2021
DOI: 10.1002/ajb2.1725
|View full text |Cite
|
Sign up to set email alerts
|

Genetic imprints of Brosimum alicastrum Sw. in Mexico

Abstract: The mechanisms generating the geographical distributions of genetic diversity are a central theme in evolutionary biology. The amount of genetic diversity and its distribution are controlled by several factors, including dispersal abilities, physical barriers, and environmental and climatic changes. We investigated the patterns of genetic diversity and differentiation among populations of the widespread species Brosimum alicastrum in Mexico. Methods: Using nuclear DNA microsatellite data, we tested whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Patterns of gene flow revealed by FEEMS could be attributable to geography, particularly the uplands to the west of TMVB and Sierra Madre del Sur, which had been previously identified by analyzing gene flow patterns for several species found on both sides of the TMVB (Anguiano‐Constante et al., 2021 ; Gándara & Sosa, 2014 ; López‐Barrera et al., 2021 ; Ruiz‐Sanchez & Ornelas, 2014 ). However, there is low differentiation between individuals north and south of the TMVB in F .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Patterns of gene flow revealed by FEEMS could be attributable to geography, particularly the uplands to the west of TMVB and Sierra Madre del Sur, which had been previously identified by analyzing gene flow patterns for several species found on both sides of the TMVB (Anguiano‐Constante et al., 2021 ; Gándara & Sosa, 2014 ; López‐Barrera et al., 2021 ; Ruiz‐Sanchez & Ornelas, 2014 ). However, there is low differentiation between individuals north and south of the TMVB in F .…”
Section: Discussionmentioning
confidence: 82%
“…In this area, it has been suggested that recent mountainous complexes, such as the Trans‐Mexican Volcanic Belt (TMVB), are main drivers of diversification in Mexico and have affected taxa in different ways (Mastretta‐Yanes et al., 2015 ). For example, in the lowlands, the TMBV has functioned as a barrier by introducing a genetic discontinuity in several species with different dispersal capabilities (Arbeláez‐Cortés et al., 2014 ; López‐Barrera et al., 2021 ; Schramm et al., 2021 ; Zarza et al., 2008 ). However, the pattern of genetic diversity and structure in the Ficus species of this region is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sex ratios were unbiased in all but one site (Zapata), in which the sex ratio was female biased (Table 1). In fragmented areas, B. alicastrum individuals are large remnant trees in small aggregations along rivers within agricultural landscapes, used by local people either as shade trees or for harvesting fruits (López‐Barrera et al, 2021). Thus, a female‐biased sex ratio in Zapata was probably associated with more intensive land use and selection of female trees for fruit harvest.…”
Section: Discussionmentioning
confidence: 99%
“…In fragmented areas, B. alicastrum individuals are large remnant trees in small aggregations along rivers within agricultural T A B L E 2 Genetic diversity estimates for each habitat condition and developmental stage of Brosimum alicastrum in two habitat conditions in the region of the Chamela-Cuixmala Biosphere Reserve, Jalisco, Mexico. landscapes, used by local people either as shade trees or for harvesting fruits (López-Barrera et al, 2021). Thus, a femalebiased sex ratio in Zapata was probably associated with more intensive land use and selection of female trees for fruit harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation